Information Systems Analysis using the Technology Acceptance Model approach. Case Study: Faculty of Engineering, Manado State University - Merriam Modeong,; Djubir R. E. Kembuan,; Olivia E. S. Liando,; Keith F. Ratumbuisang, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The information system is a technology application that provides information using the web. The Faculty of Engineering, Manado State University is an educational institution that has implemented an Information System as one of the conveniences in the student administration process starting from information on course grades received in each semester, grade point average, to filling out the Semester Plan. The use of this information system also requires both positive and negative responses. TAM is a model that is often used to measure user acceptance. With the TAM theory, it can be seen the response from users of the information system. The results of the analysis show that Perceived Usefulness, Perceived Ease of Use, and Intention are the main variables that influence User Acceptance of the information system. So, based on the analysis using TAM it can be concluded that the TAM variables are able to be a determining factor in the level of user acceptance of information systems at the Faculty of Engineering, Manado State University.